Camera Based Occupancy Detection and Lighting Control - Kamath, Vedavyasa; Padiyar U., Suprabha; Bhattacharjee, Sudipto; Charan Reddy Nayini, Sai (International Journal of Engineering and Technology, 2018)
Artificial lighting accounts for a substantial percentage of total electricity consumption in commercial and residential complexes. It is prudent to make lighting systems as efficient as possible in order to reduce consumption of electricity, which, being largely dependent on fast-depleting fossil fuel reserves, severely impacts the availability and security of resources available to future generations. One aspect of energy conservation involves developing efficient luminaires. However, the untapped potential lies in better methods of lighting control. It is necessary to shift from traditional switch-based control to intelligent controls, which minimizes human effort, while improving accuracy and savings. This paper presents a camera based lighting control system, which detects human occupancy in the control zones and controls the luminaires accordingly.Â Â Â